The role of non-stoichiometric spinel for iso-butanol formation from biomass syngas over Zn–Cr based catalysts. Issue 33 (6th April 2017) - Tian, Shaopeng; Ding, Siyi; Yang, Qianqian; Ren, Huaping; Ma, Qiang; Zhao, Yunzhen; Miao, Zongcheng
Abstract : The non-stoichiometric Zn–Cr spinel plays an essential role for the formation of iso-butanol from bio-syngas. Co-precipitation method promotes the formation of non-stoichiometric Zn–Cr spinel and dramatically enhances the catalytic performance. Abstract : A series of Zn–Cr based catalysts modified by K promoter has been prepared by different methods and their performances for iso-butanol formation from biomass syngas were investigated in a fixed bed reactor. The ZnCr-c catalyst which was prepared by co-precipitation method showed the best catalytic performance for iso-butanol formation, over which ca. 30% of CO conversion and ca. 20% of iso-butanol selectivity were achieved. Multi-characterization studies were then conducted to reveal the internal causes for different performances for iso-butanol formation over different catalysts including high resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD), X-ray absorption spectroscopy (XAS), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS). The results reveal that ZnCr-c catalyst contains the maximum amount of non-stoichiometric spinel among all the catalysts. This fact implies that the non-stoichiometric spinel is the active phase for iso-butanol synthesis from syngas. The reducibility, texture parameters and basic property of catalysts are further important factors for the formation of iso-butanol over Zn–Cr based catalysts from biomass syngas.